Physical therapy on balance and gait improvement observed within 7 days after in acute stroke: A literature review - Munkong, Mataporn; Khobkhun, Fuengfa (Journal of Thai Stroke Society, 2023)
Physical therapy is essential for movement improvement for individuals with stroke, especially in acute phase. This review article focuses on physical therapy treatments and recommendations to guide the treatment of individuals with acute stroke during the first 7 days in the hospital. The form of training and exercise includes strength training exercises in both upper and lower extremities, bed mobility, task specific practice, sitting and standing balance training, and all forms of rehabilitation innovation. The effect of physical therapy rehabilitation improves balance and gait function due to the improvement of motor and sensory systems, promoting neural plasticity, enhancing motor learning and motor control, and preventing secondary complications that may occur before hospital discharge. However, physical therapy treatment may be limited to individuals with stroke whose medical status is unstable. Therefore, clinical status is crucial and should be evaluated in individuals with stroke prior to receiving physical therapy treatment.